2018
DOI: 10.7717/peerj.5569
|View full text |Cite
|
Sign up to set email alerts
|

An integrative and citizen science based approach to the rediscovery and redescription of the only known high-altitude endemic Pill Millipede, Glomeris aurita Koch (Diplopoda, Glomerida)

Abstract: The pill millipede species Glomeris aurita Koch, 1847 remained of relative unknown origin and appearance until its recent rediscovery in samples from the Bergamasque Alps, northern Italy. In order to provide an integrative redescription and accurate identification of the high-altitude microendemic G. aurita, COI barcode sequences from three individuals coming from two different localities were obtained. These sequences are compared with those of the syntopic endemic G. oblongoguttata Verhoeff, 1894, the widesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…DNA extraction, amplification, and sequencing were conducted under identical conditions to those of earlier studies (Sagorny and Wesener 2017, Moritz and Wesener 2017, Wesener 2018, with the COI JJ primer (Astrin and Stüben 2008) being used for both PCR and sequencing. A translation into amino acids showed a similar composition to those of related species.…”
Section: Dna Extraction Attemptsmentioning
confidence: 99%
“…DNA extraction, amplification, and sequencing were conducted under identical conditions to those of earlier studies (Sagorny and Wesener 2017, Moritz and Wesener 2017, Wesener 2018, with the COI JJ primer (Astrin and Stüben 2008) being used for both PCR and sequencing. A translation into amino acids showed a similar composition to those of related species.…”
Section: Dna Extraction Attemptsmentioning
confidence: 99%
“…Whether the variation is an indicator of the presence of cryptic species of P. lagurus, or is the result of large intraspecific distances in this strictly maternal marker combined with the parthenogenetic lifestyle of the species and possible distribution by birds and wind over large distances, cannot be addressed until more detailed genetic and morphological studies are conducted. Intraspecific distances in the COI gene of widespread European species of pill millipedes (Glomerida) are usually 5% or even lower (Wilbrandt et al 2015;Wesener 2015aWesener , 2015bWesener & Conrad 2016;Reip & Wesener 2018;Wesener 2018), while interspecific distances in tropical giant pill-millipedes are usually 10% or more (Sagorny & Wesener 2017;Moritz & Wesener 2017;Wesener 2019). ), resulting in a barcoding gap between intra-and interspecific distances in the COI gene of 5-10%.…”
Section: Discussionmentioning
confidence: 99%
“…These advances in access to technology have increased the utility of participant-generated data for natural scientists and inspired new research questions. For instance, these data have documented the presence and range of rare species and morphs (Borzée et al, 2019;Wesener, 2018;Worthington et al, 2012), tracked non-native species (Gallo & Waitt, 2011;Larson et al, 2020) and revealed organismal responses to climate change and human activity (Champion et al, 2018;Des Roches et al, 2022;Sanderfoot et al, 2022;Senzaki et al, 2020). These efforts can be mutually beneficial, resulting in greater personal agency and political participation (Ballard, Dixon, et al, 2017;Conrad & Hilchey, 2011;Overdevest et al, 2004), a connection to civic and legal forums that provide legitimacy to public input (McCormick, 2012), a sense of advocacy for environmental action (Ballard, Robinson, et al, 2017;Cornwell & Campbell, 2012), increased accountability and industrial compliance with regulatory agencies (Overdevest & Mayer, 2007) and a strengthened sense of community belonging and care of the local environment (Haywood et al, 2016(Haywood et al, , 2021Newman et al, 2017;Toomey et al, 2020).…”
Section: Ebird Inaturalist and Nestwatch)mentioning
confidence: 99%